Using technology to scale climate-smart agriculture, conservation agriculture, sustainable intensification, and nutrition interventions: Why use a GESI approach? - Nortje, Karen (International Water Management Institute, 2023)
East and Southern Africa is a climate hotspot, with more than US$45 billion in agricultural production at risk from higher temperatures, shorter growing seasons, and more extreme droughts and floods. Women play a strategic role in agricultural development and food security, often in labor-intensive activities. Efforts to quickly address the current water and climate challenges through innovative ways have been underscored. One of such innovations emphasized has been production technologies, recognized as potentially effective in improving agricultural incomes for farmers. While these are positive steps, there is an increasing call for technological innovations to consider the position and dynamics of marginalized farmers by ensuring that farm equipment can be operated by both men and women, while requiring less labor and time. Hence, gender-responsive agricultural technologies should close the existing gender gaps that allow marginalized groups to fight against food insecurity. Some technologies have received increased societal resistance to adoption, especially toward innovations that are introduced as ground-breaking due to sociocultural and economic values. We assess why and how a gender-equality and social-inclusion (GESI) lens is essential as a transformative approach to achieving food and climate resilience. Using the Ukama Ustawi Initiative in East and Southern Africa, we demonstrate: i) the different types of CA/CSA/ SI interventions practiced by men and women and ii) the gender implications for farmers’ uptake and why a GESI framework is relevant. This presentation focuses on the GESI framework developed for the initiative and unpacks core innovations and how a GESI approach can influence a gender-responsive outcome.